2014
DOI: 10.1155/2014/987475
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery and HIPEC for Peritoneal Carcinomatosis in the Elderly

Abstract: Background. The combined treatment of peritoneal carcinomatosis with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy is a rigorous surgical treatment, most suitable for young and good performance status patients. We evaluated the outcomes of elderly patients undergoing CRS and HIPEC for peritoneal carcinomatosis with careful perioperative care. Methods. All consecutive patients 70 years of age or older who were treated for peritoneal carcinomatosis over the past five years were included. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
2
10
0
1
Order By: Relevance
“…Mortality of the elderly patients in our study was 3 %, which was not statistically different from the mortality of the younger patients after undergoing CRS and PIC. Similar mortality and morbidity rates for performing CRS and PIC for elderly patients as compared to younger patients have also been reported previously [ 7 – 9 , 16 , 17 ]. Although the mortality of our patients in the subgroup (i.e.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Mortality of the elderly patients in our study was 3 %, which was not statistically different from the mortality of the younger patients after undergoing CRS and PIC. Similar mortality and morbidity rates for performing CRS and PIC for elderly patients as compared to younger patients have also been reported previously [ 7 – 9 , 16 , 17 ]. Although the mortality of our patients in the subgroup (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…A recent systematic review done by Chua et al has shown an optimal morbidity rate ranging from 12 to 52 % and a mortality rate ranging 0.9 and 5.8 % [ 6 ]. A considerable number of patients with peritoneal carcinomatosis are aged 60 or older and are more commonly associated with comorbidities due to their age [ 7 , 8 ]. Thus, whether the elderly can tolerate such an invasive surgery presents a challenge for healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to account for potential confounders we used logistic regression. Specifically, in all cases we adjusted for potential effects of PCI and CCS based on prior knowledge [12] and independent of the estimated p-value; as for the rest of the confounders, we included them in the final model only if they had statistically significant results.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The operations can be summarized as follows: [19] • Since cytoreductive surgery is a major abdominal operation, with possible morbidity, good preoperative patient selection is of crucial importance, so as to identify which patients will benefit more from such an extensive procedure. While so far age over than 65 years was considered a major contraindication for cytoreductive surgery and HIPEC, [20] two recent studies by Votanopoulos et al [21] and Spiliotis et al [22] demonstrated that HIPEC can be safely performed in patients older than 70 years, with acceptable postoperative morbidity and mortality.…”
Section: Cytoreduction Techniquementioning
confidence: 99%